Gamification and the development of tourism destinations - Viana, Francisco; Costa, Vânia (Tourism and Hospitality International Journal, 2023)
According to the literature, the creation of tourist products and services using technologies to promote unique experiences allows for supporting the tourist experience and provides the creation of a bond between the tourist and the destinations. The use of games in the tourism industry is a reality applied in some tourist destinations, although the reality is still little explored. This study aims to understand the potential of Gamification and its influence on the development of tourist destinations. The methodology applied followed a mixed approach, with the application of a questionnaire survey to a sample of 216 potential consumers of tourism destinations, of which 27 respondents had previously had some experience of gamification in tourism and the remaining 189 had not. Two semi-structured interviews were also conducted with two experts, a manager in the tourism sector and a computer engineer, in order to gather qualitative information from technical experts involving the two areas. The study concluded that gamification can create new experiences and improve visitation, making the destination more attractive and interactive for visitors, appearing as a differentiating element of the destination and being able to reduce seasonality. The sample that had never been in contact with gamification showed great interest and curiosity in using this content if they had the opportunity.